Signifikansi Nilai Pendidikan Multikultural dalam Animasi Upin dan Ipin terhadap Sikap Toleransi Beragama - Al Ihwanah Al Ihwanah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2018)
Indonesian society is diverse culture and religion. It wants the next generation to have an attitude of religious tolerance. This attitude of tolerance can be nurtured from a basic age. In the present age children have a love interest animated series either through the media of television, gadgets, or the internet. The animated series that are often watched are Upin and Ipin. In the animation is portrayed the main character of Islam but familiar with different cultural friends and different religions. This study analyzed the value of multicultural education in Upin and Ipin animation series, and its significance to the religious tolerance of children. Based on interviews, field observations, and the reading of the animated film series Upin Ipin, this article argues that the multicultural values ??in Upin and Ipin animation series have significance in fostering the attitude of religious tolerance of Elementary School students.